A potential role of endoplasmic reticulum stress in development of ovarian hyperstimulation syndrome. (15th June 2016) - Takahashi, Nozomi; Harada, Miyuki; Hirota, Yasushi; Zhao, Lin; Yoshino, Osamu; Urata, Yoko; Izumi, Gentaro; Takamura, Masashi; Hirata, Tetsuya; Koga, Kaori; Wada-Hiraike, Osamu; Fujii, Tomoyuki; et al.
Abstract: Vascular endothelial growth factor A (VEGFA) is crucial for ovarian angiogenesis, but its excess production induces ovarian hyperstimulation syndrome (OHSS). The aim of this study was to determine whether endoplasmic reticulum (ER) stress regulates VEGFA expression in granulosa cells, and whether its activation is involved in OHSS development. The expression of the spliced form of X-box-binding protein 1 [XBP1(S)], induced by ER stress, in cumulus cells from OHSS patients was higher than that in cumulus cells from non-OHSS patients. The ER stress inducer tunicamycin increased human chorionic gonadotropin-induced VEGFA production in human granulosa cells through the induction of XBP1(S), and pretreatment with the ER stress inhibitor tauroursodeoxycholic acid (TUDCA) abrogated the effect of tunicamycin. In OHSS model rats, TUDCA administration prevented the OHSS development, reducing ovarian VEGFA production. Our findings suggest ER stress upregulates hCG-induced VEGFA production in granulosa cells, indicating that ER stress might be involved in OHSS development. Highlights: Cumulus cells from patients who developed OHSS are under greater ER stress. ER stress upregulates hCG-induced VEGFA production in granulosa lutein cells. An ER stress inhibitor prevents OHSS by reducing ovarian VEGFA production. ER stress represents a novel therapeutic target for prevention of OHSS.